Regulatory Advocacy Update: American Society of Plastic Surgeons Comments in Response to the U.S. Food and Drug Administration Draft Guidance Documents on Human Cell and Tissue Products. Issue 5 (May 2017) - Rubin, J. Peter; D'Amico, Richard A.; Rodriguez, Ricardo; Coleman, Sydney R.; Cederna, Paul; Glasberg, Scot; Neumeister, Michael; Song, David H.; Butler, Charles; Hume, Keith M.
Abstract : Summary: The U.S. Food and Drug Administration released draft guidance documents on human cells, tissues, and cellular and tissue-based products regulations. These proposed guidance documents can impact the practice of plastic surgery in the area of tissue grafting procedures. This article describes the relevant issues in these draft guidance documents, and presents the comments provided to the U.S. Food and Drug Administration by the American Society of Plastic Surgeons. Abstract : Supplemental Digital Content is available in the text.